SEASONAL VARIATION OF THE CHEMICAL CONSTITUENTS OF THE ESSENTIAL OIL OF THE LEAVES FROM Ophryosporus peruvianus - Mattos Vila, Edith María Fernanda (2020)
The ephemeral shrub Ophryosporus peruvianus was collected for five months (December 2018 – April 2019) in Andahuaylallas (Cusco). The oil essential from leaves of the bush was obtained by hydrodistillation and analyzed by gas chromatography coupled to a mass spectrometer. Eigthy nine components of the essential oil were identified among oxygenated monoterpenes, sesquiterpenes hydrocarbons, sesquiternes oxygenated, oxygenated diterpenes, among others, of which the major components were the sesquiterpenes hydrocarbons β-caryophyllene, (Z)-β-Farnesene y β-Sesquiphellandrene and were presents in the samples of the five months of collection.